Anti‐inflammatory treatment rescues memory deficits during aging in nfkb1−/− mice. Issue 10 (11th September 2020) - Fielder, Edward; Tweedy, Clare; Wilson, Caroline; Oakley, Fiona; LeBeau, Fiona E. N.; Passos, João F.; Mann, Derek A.; von Zglinicki, Thomas; Jurk, Diana
Abstract: Chronic inflammation is a common feature of many age‐related conditions including neurodegenerative diseases such as Alzheimer's disease. Cellular senescence is a state of irreversible cell‐cycle arrest, thought to contribute to neurodegenerative diseases partially via induction of a chronic pro‐inflammatory phenotype. In this study, we used a mouse model of genetically enhanced NF‐κB activity ( nfκb1 −/− ), characterized by low‐grade chronic inflammation and premature aging, to investigate the impact of inflammaging on cognitive decline. We found that during aging, nfkb1 −/− mice show an early onset of memory loss, combined with enhanced neuroinflammation and increased frequency of senescent cells in the hippocampus and cerebellum. Electrophysiological measurements in the hippocampus of nfkb1 −/− mice in vitro revealed deficits in gamma frequency oscillations, which could explain the decline in memory capacity. Importantly, treatment with the nonsteroidal anti‐inflammatory drug (NASID) ibuprofen reduced neuroinflammation and senescent cell burden resulting in significant improvements in cognitive function and gamma frequency oscillations. These data support the hypothesis that chronic inflammation is a causal factor in the cognitive decline observed during aging. Abstract : Chronic inflammation induces cellular senescence and leads to premature aging and cognitive decline. Anti‐inflammatory treatment reduces neuroinflammation and senescent cell burden, and ameliorates cognitive impairment.